2020
DOI: 10.3389/fonc.2020.01121
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Based on CECT in Differentiating Kimura Disease From Lymph Node Metastases in Head and Neck: A Non-Invasive and Reliable Method

Abstract: Background: Kimura disease may be easily misdiagnosed as malignant tumors such as lymph node metastases based on imaging and clinical symptoms. The aim of this article is to investigate whether the radiomic features and the model based on the features on venous-phase contrast-enhanced CT (CECT) images can distinguish Kimura disease from lymph node metastases in the head and neck. Methods: A retrospective analysis of 14 patients of head and neck Kimura disease (a total of 38 enlarged lymph nodes) and 39 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Feature pre-processing was done in two steps: step 1-outliers and null values were replaced by mean values, and step 2-values standardization was carried out to eliminate the influence of the dimension (14). Feature selection is a critically important step for better generalization of models because high-dimensional data usually comprise a large number of irrelevant, redundant, and noisy features, which may result in the curse of dimensionality and model overfitting (15).…”
Section: Feature Pre-processing and Selectionmentioning
confidence: 99%
“…Feature pre-processing was done in two steps: step 1-outliers and null values were replaced by mean values, and step 2-values standardization was carried out to eliminate the influence of the dimension (14). Feature selection is a critically important step for better generalization of models because high-dimensional data usually comprise a large number of irrelevant, redundant, and noisy features, which may result in the curse of dimensionality and model overfitting (15).…”
Section: Feature Pre-processing and Selectionmentioning
confidence: 99%
“…All LNs (N = 201) were randomly divided into 2 subsets in a 7:3 ratio ( 29 31 ). Seventy percent (N = 140) were assigned to the training set by stratified sampling, including 84 malignant cases (60%, 84/140) and 56 benign cases (40%, 56/140).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have also shown its potential in differentiating benign from malignant lesions. For example, Zhang et al [ 16 ] were able to distinguish Kimura disease from LN metastases by means of radiomics analysis on CECT scans. Kimura disease is a rare lymphoproliferative disease, which consists of painless subcutaneous soft tissue masses and goes along with an enlargement of LNs in the head and neck region, therefore easily being confused with LN metastases of an occult primary tumor.…”
Section: Introductionmentioning
confidence: 99%